Adaptation for Regulatory Application: A Content Analysis of FDA Risk Evaluation and Mitigation Strategies Assessment Plans (2014–2018) Using RE-AIM - Toyserkani, Gita A.; Huynh, Linda; Morrato, Elaine H. (Frontiers in Public Health, 2020)
Background: Risk Evaluation and Mitigation Strategies (REMS) are safety programs that U.S. Food and Drug Administration can require to ensure a drug's benefits outweigh its risks and can be considered public health interventions. FDA's 2019 draft Guidance for Industry on REMS Assessments encourages the development of “novel methods for assessing REMS [to] help advance the science of post-market assessment of effectiveness of risk mitigation strategies.” Objective: To characterize REMS assessment plans using RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework and identify areas for advancing methods for evaluating REMS programs. RE-AIM was selected for its wide application evaluating the translation of scientific advances into practice for public health impact. Methods: A content analysis of REMS assessment plans (N = 18) and measures(n = 540) was conducted for REMS programs approved by FDA between 1/1/2014–12/31/2018. Eligibility criteria were: a new drug application or biologic license application, included FDA-mandated mitigation strategies called elements to assure safe use (ETASU), and represented a single product REMS program. Assessment plans were collected from publicly available regulatory approval letters from REMS@FDA website. Blinded reviewers categorized each REMS assessment measure to a RE-AIM dimension, adjudicated their application (average IRR 75%), and refined the adapted dimensions' definitions. Dimensions were also mapped to REMS Assessment guidance categories. Results: The median number of assessment measures per REMS assessment plan was 31 (IQR: 21–36). Frequency of measures per RE-AIM criteria per REMS program was: Reach (median = 2; IQR: 2–4); Effectiveness (median = 2.5; IQR:1–4); Adoption (median = 3.5; IQR: 2–5); Implementation (median = 18; IQR: 15–24); Maintenance (median = 0; IQR: 0–1). Adoption (among prescriber, health system agents of implementation) was more commonly assessed than Reach (population-attributable number of patients affected). Assessment of heterogeneity of Adoption and Reach was generally absent. Implementation assessment measures were most common among drugs requiring evidence of safe-use conditions before dispensing or administering the drug. Patient-level Effectiveness and Maintenance assessments were most common among drugs requiring patient monitoring. Discussion: Implementation science frameworks, such as RE-AIM, can be applied to characterize REMS assessment measures and identify opportunities for standardizing and strengthening their evaluation. Methods to measure Maintenance are needed to provide real-world evidence of REMS integration into the healthcare system.